Aeromonas sobria Induced Sepsis Complicated with Necrotizing Fasciitis in a Child with Acute Lymphoblastic Leukemia - Manuela Colosimo; Maria Concetta Galati; Umberto Riccelli; Simona Paola Tiburzi; Eulalia Galea; Teresa Alcaro; Orazio Stefano Giovanni Filippelli; Francesco Abbonante; Pasquale Minchella; Luca Gallelli (Reports, 2021)
Aeromonas species are gram negative and able to induce systemic diseases (i.e., gastrointestinal, respiratory, and cardiovascular, diseases, in addition to infection of brain and soft tissues). In this study, we describe the development of necrotizing fasciitis in a young immunocompromised girl, with a low response to drug treatment and who died after some months.